Pengaruh Lingkungan Kerja Dan Kinerja Karyawan Terhadap Kelancaran Ekspor Benang di PT. Bitratex Industries Semarang - Dian Shinta Devitasari; Evyana Diah Kusumawati; Tini Utami (JURNAL TRANSMA, 2025)
The purpose of this study was to examine the effect of employee performance and work environment on the smooth yarn export of PT Bitratex Industries Semarang. Associative quantitative research is the type of this research. The research sample amounted to 92 people, while the population amounted to 1,097 workers of PT Bitratex Industries Semarang. Simple Random Sample or SRS is a probability sampling approach. The data collection techniques used are observation, interview, documentation, and questionnaire distribution. Based on the partial T test results (X1 (work environment) tcount value 4.299> ttable 1.987), then Ho1 is rejected and Ha1 is accepted because there is a positive and significant influence. Employee performance has a positive and significant influence on the smooth export of yarn, then Ho2 is rejected and Ha2 is accepted based on the results of the partial T test X2 (employee performance) tcount value 4.540> ttable 1.987. Based on the results of the F test (simultaneous) variable Y (smooth yarn exports) obtained a value of fcount 66.314> ftable 3.10, then Ho3 is rejected and Ha3 is accepted, this indicates that the work environment and employee performance together have a positive and significant effect on the smooth export of yarn. The two independent variables have an effect of 59.8% on the smooth export of yarn.